(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
A HPLC method has been described for simultaneous determination of Paracetamol, Phenylpropanolamine hydrochloride and Cetirizine hydrochloride in formulation. This method is based on HPLC separation of the three drugs on the Thermo Hypersil Gold C18 column (250 mm × 4.6 mm, 5.0µ), with isocratic conditions and mobile phase containing methanol: 0.01M disodium hydrogen phosphate dihydrate buffer [pH 7, adjusted with Ortho Phosphoric Acid (OPA)] (60: 40) at a flow rate of 1 ml/min, using UV detection at 217 nm. This method has been applied to formulation without any interference of excipients of formulation. The linear regression analysis data for the calibration plots showed a good linear relationship over the concentration range of 0.4-1.4µg/ml for Paracetamol, 7-12µg/ml for Phenylpropanolamine hydrochloride and 5-10µg/ml for Cetirizine hydrochloride respectively. The mean values of the correlation coefficient, slope and intercept were 0.9993, 51489 and 5844.4 for Paracetamol, 0.9991, 23235 and 70540 for Phenylpropanolamine hydrochloride and 0.9990, 40416 and 93404 for Cetirizine hydrochloride respectively. The method was validated as per the ICH guidelines. The limit of detection (LOD) and limit of quantitation (LOQ) was 0.2μg/ml and 0.4μg/ml for Paracetamol, 5μg/ml and 7μg/ml for Phenylpropanolamine hydrochloride and 4µg/ml and 5µg/ml for Cetirizine hydrochloride, respectively. Statistical analysis showed that the method is repeatable and selective for the estimation of Paracetamol, Phenylpropanolamine hydrochloride and Cetirizine hydrochloride.